2011
DOI: 10.1002/mats.201100025
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization Effects on Bimolecular Termination in Atom Transfer Radical Polymerization in Nanoreactors

Abstract: The factors that determine the magnitude of the segregation effect in atom transfer radical polymerization (ATRP) in a dispersed system (miniemulsion, emulsion, etc.) have been elucidated by means of simulations based on two‐dimensional Smith–Ewart equations. The segregation effect is not a function of merely the average number of propagating radicals per particle, but also depends on the values of the deactivation and termination rate coefficients. This occurs as a result of these rate coefficients exerting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…As outlined above, in both NMP and ATRP, the kinetic effect of compartmentalization is typically manifested as the segregation effect on termination and the confined space effect on deactivation. From the perspective of rationalizing such effects, NMP and ATRP can be treated under a single umbrella given that both are based on the persistent radical effect. , The same kinetic treatment applies to both NMP ,,,, and ATRP , if one simply replaces “ k act ” in NMP by “ k act [Cu­(I)]” (illustrated with Cu­(I) as the activating complex in ATRP). In what follows, compartmentalization effects are first explained within the framework of miniemulsion NMP with possible thermal self-initiation ( k i,th ; styrene (St) case (L 2 mol –2 s –1 )) and ignoring exit/entry events.…”
Section: Compartmentalization In Nmp and Atrpmentioning
confidence: 99%
“…As outlined above, in both NMP and ATRP, the kinetic effect of compartmentalization is typically manifested as the segregation effect on termination and the confined space effect on deactivation. From the perspective of rationalizing such effects, NMP and ATRP can be treated under a single umbrella given that both are based on the persistent radical effect. , The same kinetic treatment applies to both NMP ,,,, and ATRP , if one simply replaces “ k act ” in NMP by “ k act [Cu­(I)]” (illustrated with Cu­(I) as the activating complex in ATRP). In what follows, compartmentalization effects are first explained within the framework of miniemulsion NMP with possible thermal self-initiation ( k i,th ; styrene (St) case (L 2 mol –2 s –1 )) and ignoring exit/entry events.…”
Section: Compartmentalization In Nmp and Atrpmentioning
confidence: 99%
“…has explored the use of bifunctional initiators and its implications in the synthesis of triblock copolymers . Other works have investigated the effects of compartmentalization on kinetics and control in disperse systems containing nanometric particles as reaction sites (e.g., miniemulsion and microemulsion ATRP polymerizations) . D'hooge et al have reported an interesting methodology to study normal ATRP, based on an extension of the moments method, using the Quasi Steady State Approximation (QSSA) for the active polymer chains and computing the diffusional limitations by using the average apparent rate constants .…”
Section: Introductionmentioning
confidence: 99%
“…The polymer MWD can be better understood and controlled by using mathematical models that describe its evolution during the synthesis reaction. Previous mathematical modeling of ATRP has been done by a number of research groups, but most of that research focused on previous versions of ATRP, especially early works trying to better understand the kinetics and mechanism of these processes. In contrast, a few have been done on the modeling of ICAR and ARGET systems, which have greater industrial potential.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, the design of well-tailored polymers molecules with predetermined number average chain length, high end-group functionality (EGF), controlled topology and low dispersity has been the topic of many research activities [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These advanced macromolecular architectures are typically acquired via controlled radical polymerization (CRP), which is also known as reversible deactivation radical polymerization (RDRP).…”
Section: Introductionmentioning
confidence: 99%